2001
DOI: 10.1021/bi010431+
|View full text |Cite
|
Sign up to set email alerts
|

Hormonal Regulation of Peripheral Benzodiazepine Receptor Binding Properties Is Mediated by Subunit Interaction

Abstract: The peripheral benzodiazepine receptor (PBR) is composed of three subunits with molecular masses of 18, 30, and 32 kDa. Many physiological functions have been attributed to the PBR, including regulation of steroidogenesis. Furthermore, the PBR itself is under hormonal regulation. In the current study, we investigated the role of female gonadal sex hormones in the regulation of PBR expression in steroidogenic and nonsteroidogenic tissues. To accomplish this, adult female rats were pharmacologically castrated us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(40 citation statements)
references
References 52 publications
(85 reference statements)
1
39
0
Order By: Relevance
“…VDAC1 levels were reduced following 2-h treatment with hCG. It has been shown that the ratio of TSPO to VDAC and ANT can be modulated by hormone treatments (48). However, the significance of this finding in steroidogenesis remains to be determined.…”
Section: Discussionmentioning
confidence: 99%
“…VDAC1 levels were reduced following 2-h treatment with hCG. It has been shown that the ratio of TSPO to VDAC and ANT can be modulated by hormone treatments (48). However, the significance of this finding in steroidogenesis remains to be determined.…”
Section: Discussionmentioning
confidence: 99%
“…It has been hypothesized that the close association of TSPO with VDAC (Gavish et al, 1999;McEnery et al, 1992) may help to ensure that the ROS generated via TSPO can actually affect VDAC. The reported grouping of TSPO molecules around VDAC, potentially reflecting TSPO polymerization (Golani et al, 2001;Veenman et al, 2002Veenman et al, , 2007, may help enhance the concentration of ROS generated by TSPO in the proximity of the VDAC, leading to apoptosis induction (see Section 9.3).…”
Section: Vdac and The Translocator Proteinmentioning
confidence: 99%
“…TSPO is mainly found on the OMM [340,345], where it is closely associated with VDAC [346]. It has been hypothesized that the close association of TSPO with VDAC allows ROS generated via TSPO to affect VDAC [296,347]. In addition, the reported grouping of TSPO molecules around VDAC, potentially reflecting TSPO polymerization [296,348], could enhance the concentration of ROS generated by TSPO in the proximity of VDAC, leading to apoptosis induction [296,349,350].…”
Section: Translocator Protein (Tspo) and Vdac1mentioning
confidence: 99%